The wide‐ranging life outcome correlates of a general psychopathology factor in adolescent psychopathology. (13th August 2019) - Laceulle, Odilia M.; Chung, Joanne M.; Vollebergh, Wilma A.M.; Ormel, Johan
Abstract: Background: The structure of psychopathology has been much debated within the research literature. This study extends previous work by providing comparisons of the links between psychopathology and several life outcomes (temperamental, economic, social, psychological and health) using a three‐correlated‐factors model, a bifactor model, a revised‐bifactor model and a higher‐order model. Methods: Data from a sample of Dutch adolescents were used ( n = 2 230), and psychopathology factors were modelled using self‐reported and parent‐reported longitudinal data from youth across four assessments during adolescence, from ages 11 to 19. Outcome variables were assessed at age 22 using adolescent‐reports and parent‐reports and more objective measures (e.g. body mass index). Results: While no measurement model was clearly superior, we found modest associations between the psychopathology factors and life outcomes. Importantly, after taking into account a general factor, the associations with life outcomes decreased for the residual parts of thought problems (across all domains) and internalizing problems (for temperamental and psychological outcomes), but not for externalizing problems, compared with the traditional three‐correlated‐factors model. Patterns were similar for adolescent‐reported and parent‐reported data. Conclusions: Findings suggest that a general factor is related to psychopathology and life outcomes in a meaningful way. Results are discussed in terms of individual differences in propensity to psychopathology and more broadly in light of recent developments concerning the structure of psychopathology. © 2019 The Authors Personality and Mental Health Published by John Wiley & Sons Ltd